INTEGRATING DUOLINGO ENGLISH TEST (FREE PRACTICE) IN EFL SPEAKING INSTRUCTION: A QUASI-EXPERIMENTAL STUDY AT UNIVERSITAS NEGERI MEDAN - Tumanggor, Edward Johannes; Annisa, Puan Suri Mira; Syahputri, T. Mira; Br. Bangun, Emia Ninta; Arsita, Dwi Mas; Tambunan, Anastasya Bela Pertiwi (Universitas Islam Sumatera Utara, 2025)
English speaking ability, a primary competency for English Education students, is often hindered by limited practice, lack of confidence, and minimal independent learning media. This study investigates the effectiveness of the Duolingo English Test (Free Practice) platform as a digital learning medium within the Receptive Oral Language Skills course to enhance students' English speaking abilities. This study uses a quantitative approach with a one-group quasi-experimental design, involving a pre-test and post-test to measure improvement before and after the intervention. The intervention consisted of routine practice using the Duolingo platform and supplementary materials from the